Pathways, through opportunity, towards social inclusion: a multiple case study of young womxn in marginalising contexts in post-apartheid South Africa - Peters, Liesl (Department of Health and Rehabilitation Sciences, 2025)
Background Post-apartheid South Africa promised a born-free generation, but young people are not always able to participate in ways that allow them to live freely. Race, class and gender continue to be designated markers of particular life trajectories as young people operate from historically oppressed race, class and gender positions. Young womxn from and in such marginalising contexts experience an array of challenges that place them at risk of an experience of waithood and social exclusion. Various iterations of South African youth policies have suggested that certain kinds of opportunities could play a pivotal role in contributing to more prosperous futures for young people. Previous research concurs. However, the solutions offered through these policies have not resulted in an experience of different futures for young womxn at risk of social exclusion. An exploration of relevant literature on key concepts and related studies in occupational science, and other aligned disciplines, revealed the fragmented and static understanding that existed at the inception of this study about opportunity as a phenomenon that contributes to just and equitable outcomes. As such, critical and socially transformative occupational therapy and occupational science, as the broad grounds for the scholarly work presented in this thesis, have not contributed sizeable solutions to the problems of exclusion facing young people in South Africa. Notwithstanding, young womxn from and in marginalising contexts are capable of agency, demonstrating a responsiveness to social conditions that defies a victory of structure in 1 conclusively predetermining their experiences of everyday life. Examples exist of young womxn who have opened and walked their own pathways towards social inclusion. The need to learn from and with these young womxn was the focus of this research study. The aim of this study was therefore: To explore and describe how young womxn from and in marginalising contexts move towards experiences of social inclusion, through opportunity, in post-apartheid South Africa. Methods A merged theoretical perspective, including decoloniality as a form of critical social theory and the theory of structuration, oriented the understanding of the praxis of living for young womxn from and in marginalising contexts in South Africa. Such a perspective was central for apprehending the relational aspects of agency and structure in young womxn's lives, and how these played out in a context heavily shaped by apartheid and coloniality. The phenomenon explored in this study was defined as the movement of young womxn towards an experience of social inclusion, through opportunities. A qualitative, multiple case study design was applied, drawing on narrative inquiry as a key approach. Using purposive sampling and guided by selection advisors, three young womxn from different communities in the Western Cape Province of South Africa - who believed they were experiencing a more prosperous life that they likened to an experience of social inclusion - were selected to participate in the study. These womxn were willing to offer up their life histories as individual cases that we could explore and learn from. An array of data sources and data generation methods were used to construct each individual case narrative, utilising multiple perspectives. These included life history interviews, in-depth interviews and focus groups with people who were part of each young womxn's life, document analysis and observation. Participants also introduced artifacts which complimented and developed the understanding of their life trajectories. A narrative analytic approach supported the interpretive process to develop within-case inferences about the phenomenon, as it had manifested within the unique circumstances of each case. Following this, a cross-case analysis was conducted to develop an explanation of 2 the phenomenon. Trustworthiness was assured through a range of methods, the most important of which included multiple triangulation approaches, reflexive journaling, and a process of member checking that ensured the veracity of the individual case narratives. Further, data was generated over a prolonged period. These methods provided the foundation for a credible cross-case analysis. The study received ethical approval from the Faculty of Health Sciences Human Research Ethics Committee at the University of Cape Town. Strategies that ensured the ethical conduct of the study were applied throughout, with minimal risk to participants. Of central importance was the maintenance of confidentiality, since intricate and in-depth details were part of participants' life histories. This risk was mitigated by changing minor details that did not adversely affect the credibility of the data and protected the anonymity of participants. All participants expressed the benefits associated with having been able to share their experiences through the data generation processes in the study. Findings and Discussion The analytic process led to the development of an overarching intuition, comprised of a set of inferences, that illustrated that the way young womxn from and in marginalising contexts move towards social inclusion, through opportunity, is through the process of making-a-life. Making-a-life was understood as a uniquely crafted political praxis that is given impetus through a meshwork of lifelines, co-creating the likelihood of young womxn reaching towards social inclusion. Theorising this notion generated the key thesis in this study: that making-a-life is an ontogenetic praxis of correspondences that is routed within the meshwork. Making-a-life improvises with opportunities as possibilities-in-the-making, that must cohere within the context of young womxns' everyday lives to contribute valuably to this praxis. The cumulative result is the evolution of transgressive and generative agencies that operationalise a different social positioning for young womxn from and in marginalising contexts, making it possible to subvert the intentions of the modern/colonial post-apartheid context. Taking up these insights within the disciplines of occupational science and occupational therapy will require us to think relationally about agency, structure, opportunity and 3 occupation in ways that are acentred from the individual. The idea of making-a-life calls for a more explicit grasp of the relational and co-creational flows of doing over time. Conclusion and Implications The conceptualisation of pathways towards social inclusion, as acentred from young womxn as individuals, offers a new way to think about the focal point in youth interventions and policy options. This creates a space to reorient our practices towards understanding how to protect the integrity of the meshwork and create the coherence between opportunities and young womxn's everyday lives. Such actions/approaches have the potential to generate new vistas for the social inclusion of young womxn from and in marginalising contexts.